Depression and resilience levels as predictors of suicidal ideation in early adults - Selawa, Anastasia Vianna; Siswanto, Siswanto (University of Muhammadiyah Malang, 2025)
Suicide is a manifestation of suicidal ideation and is associated with poor psychological adjustment and functioning. Depression is one of the factors in the emergence of suicidal ideation, and resilience levels play a role in this phenomenon. This study aimed to determine the role of depression and resilience levels as predictors of suicidal ideation in early adults. This research used a correlational quantitative method. The participants were early adults (n=139) consisting of males (n=2) and females (n=137) aged 18-40 years who had experienced suicidal ideation (in the past year). The sampling method used was the purposive sampling technique. The instruments used were the Indonesian versions of the Beck Scale for Suicidal Ideation (BSSI), the Center for Epidemiologic Studies Depression Scale (CES-D), and the Brief Resilience Scale (BRS). Multiple linear regression test results showed that depression and resilience levels predicted suicidal ideation in early adults (R2 = 0.358; 0.000; p<0.01). The practical contribution of both predictors was 35.8%. The implications of this research can be applied in the health field, particularly clinical psychology, to reduce suicide rates so that psychologists can provide intervention efforts to reduce depression symptoms and preventive efforts by increasing individual resilience levels.